Investigation in to the types of teacher-student relationship in institution of learning in Yobe State, Nigeria - Kolo, Ali Garba; Baba, Umar Sale; Babayo, Ahmed; Wan Jaafar, Wan Munira (2018)
The study focuses on the types of teacher-student relationship in Federal Polytechnic, Damaturu,Yobe State, Nigeria.In the research a total of 312 respondents was selected through stratified and simple random sampling method. The findings revealed that, the most prevalence types of teacher-student relationship in the school was authoritarian (paternalistic 69.23%) while on the most effective types of teacher-student relationship therapist (89.1%) appeared as the strongest variable for smooth teacher-student relationship in the Polytechnic. The study recommend that: The management of the Polytechnic should devise an effective method of monitoring teacher student relationship; such as use of questionnaire, telephone lines for complaints from the students etc. should be exploited to elicit responses from students on their relationship with teachers. Both students and teachers should be discouraged from answering relationship on religion, family ties and personality influence. Teachers should treat everybody the same way irrespective of religion or influence of the person. Students should always learn to be punctual in their class and follow teachers’ instruction. Most teachers loosed interest in student, if they discover the student does not keep appointment or follow their instruction and committed to service within the profession. They should also be supportive, human and friendly to students. It is believed that these recommendations would enhance teacher student relationship in Damaturu Polytechnic and other institution of learning in the State and world at large